Hydrogeological Model of an Urban City in a Coastal Area, Case study: Semarang, Indonesia - Putranto, Thomas; RÃ¼de, Thomas (Geological Agency, 2016)
DOI:10.17014/ijog.3.1.17-27In Semarang City, groundwater has been exploited as a natural resource since 1841. The groundwater exploited in deep wells is concentrated in confined aquifers. The previous hydrogeological model was developed in one unit of aquifer and refined then by using several hydrostratigraphical units following a regional hydrogeological map without any further analysis. At present, there is a lack of precise hydrogeological model which integrates geological and hydrogeological data, in particular for multiple aquifers in Semarang. Thus, the aim of this paper is to develop a hydrogeological model for the multiple aquifers in Semarang using an integrated data approach. Groundwater samples in the confined aquifers have been analyzed to define the water type and its lateral distribution. Two hydrogeological cross sections were then created based on several borelog data to define a hydrostratigraphical unit (HSU). The HSU result indicates the hydrogeological model of Semarang consists of two aquifers, three aquitards, and one aquiclude. Aquifer 1 is unconfined, while Aquifer 2 is confined. Aquifer 2 is classified into three groups (2a, 2b, and 2c) based on analyses of major ion content and hydrostratigraphical cross sections.